Some properties of DNA-dependent RNA polymerase from Streptomyces granaticolor - Rysavý, P; Spízek, J; Klégr, M; Janecek, J; Náprstek, J; Houstĕk, J (Folia microbiologica, 1985)
RNA nucleotidyltransferase from Streptomyces granaticolor was purified and some of its properties were investigated. The temperature optimum of the enzyme is 35 degrees C, pH optimum 7.8-8.4. Antibodies against the beta subunit of the enzyme from Bacillus subtilis immunologically cross-react with the beta subunit of the enzyme from S. granaticolor. Antibodies against the beta' subunit of the enzyme from B. subtilis immunologically cross-react with both beta and beta' subunits of the enzyme from S. granaticolor.
Keywords: Bacillus subtilis; antisérum; Cross Reactions; koncentrace vodíkových iontů; DNA-Directed RNA Polymerases; termodynamika; DNA řízené RNA-polymerasy; Immune Sera; kinetika; Hydrogen-Ion Concentration; zkřížené reakce; Kinetics; Thermodynamics; Streptomyces